2023
DOI: 10.3390/nano13061016
|View full text |Cite
|
Sign up to set email alerts
|

From Nano-Crystals to Periodically Aggregated Assembly in Arylate Polyesters—Continuous Helicoid or Discrete Cross-Hatch Grating?

Abstract: This work used several model arylate polymers with the number of methylene segment n = 3, 9, 10, and 12, which all crystallized to display similar types of periodically banded spherulites at various Tc and kinetic factors. Universal mechanisms of nano- to microscale crystal-by-crystal self-assembly to final periodic aggregates showing alternate birefringence rings were probed via 3D dissection. The fractured interiors of the birefringent-banded poly(decamethylene terephthalate) (PDT) spherulites at Tc = 90 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Similar to the work on PTT or other polyesters, an earlier analysis of the top surface and internal analysis perspectives of neat PDT (10 methylene segments in chemical repeat unit) crystallized at T c = 80-95 • C has been described by Yang et al [60]. The ring-banded PDT spherulites are composed of cyclic patterns of a protruded ridge and a flat-plane untextured valley area, as viewed from the top surface.…”
Section: Periodic Microstructures and Iridescent Features Of Pot And Pntmentioning
confidence: 80%
“…Similar to the work on PTT or other polyesters, an earlier analysis of the top surface and internal analysis perspectives of neat PDT (10 methylene segments in chemical repeat unit) crystallized at T c = 80-95 • C has been described by Yang et al [60]. The ring-banded PDT spherulites are composed of cyclic patterns of a protruded ridge and a flat-plane untextured valley area, as viewed from the top surface.…”
Section: Periodic Microstructures and Iridescent Features Of Pot And Pntmentioning
confidence: 80%
“…Linear retardance (LR) is the path difference gained by orthogonal polarization modes vibrating in anisotropic crystals that is proportional to the intrinsic difference in refractive activity, as well as the path length. Woo et al observed that spherulites with incoherent twisted fibers have lower LR compared to spherulites with coherent fibers. , In other words, coherent fibers better approximate the LR of a single crystal. Here, we measured LR for twisted coumarin crystals with different boundary incoherence using Mueller matrix microscopy (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Woo et al observed that spherulites with incoherent twisted fibers have lower LR compared to spherulites with coherent fibers. 25 , 26 In other words, coherent fibers better approximate the LR of a single crystal. Here, we measured LR for twisted coumarin crystals with different boundary incoherence using Mueller matrix microscopy ( Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prof. Woo and colleagues [9] studied the self-assembly of model arylate polyester polymers with different numbers of methylene segments (n = 3, 9, 10, and 12) in solid state. These polymers crystallized depending on the conditions as similar types of periodically banded spherulites.…”
mentioning
confidence: 99%